A sirtuin activator and an anti-inflammatory molecule—multifaceted roles of adjudin and its potential applications for aging-related diseases. (November 2016) - Xia, Weiliang; Geng, Keyi
Abstract: Adjudin was originally developed as an improved analog of lonidamine to serve as a non-hormonal reversible male contraceptive that could cause exfoliation of the immature sperms from the seminiferous epithelium. Recently, the functionality spectrum of adjudin expands beyond as an anti-spermatogenic agent, namely, it could function as an anti-cancer drug potentially useful for combination chemotherapy, and as an anti-inflammatory molecule that could protect against ischemic stroke injury. Most strikingly, adjudin acts through activation of mitochondrion-located Sirt3 to safeguard hair cells of the cochlea from ototoxicant such as gentamycin. Recent studies also indicate that adjudin could attenuate oxidative stress and cellular senescence. These findings suggest wider applications of this small molecule, particularly in aging-related diseases.